Pengendapan Uranium dan Thorium Hasil Pelarutan Slag II - Anggraini, Mutia; Sarono, Budi; Waluyo, Sugeng; Rusydi, Rusydi; Sujono, Sujono (EKSPLORIUM, 2015)
Tin smelting process produces waste in the form of large amount of slag II. Slag II still consist of major elements such as 0.0619% uranium, 0.530% thorium, 0.179% P2O5 and 6.194% RE total oxide. Based on that fact, the processing of slag II is interesting to be researched, particularly in separating uranium and thorium which contained in slag II. Uranium and thorium dissolved using acid reagent (H2SO4). Percentage recovery of uranium, thorium, phosphate and RE oxides by dissolution method are 98.52%, 83.16%, 97.22%, and 69.62% respectively. Dissolved uranium, thorium, phosphat, and RE were each precipitated. The factors which considerable affect the precipitation process are reagent, pH, temperature, and time. NH4OH is used as precipitation reagent, optimum condition are pH 4. Temperature and time reaction did not influence this reaction. Percentage recovery of this precipitation process at optimum condition are 93.84% uranium and 84.33% thorium.